Coeliac disease: Reappraisal of clinical diagnosis. Issue 249 (October 1971) - Cook, D. M.; Evans, N.; Lloyd, Anne; Stewart, J. S.
Abstract : Twelve children previously diagnosed as having coeliac disease on criteria now regarded as incomplete have been reinvestigated. Six were found to have an intestinal mucosal lesion characteristic of coeliac disease. All but one had been asymptomatic on a normal diet for more than 18 months. Response to diet fails to distinguish between coeliacs and non-coeliacs. Establishing the diagnosis of coeliac disease by intestinal biopsy is essential, since even apparently symptomless individuals are at considerable risk.